Influence of injectable microparticle size on cardiac progenitor cell response. Issue 4 (October 2018) - Rosellini, Elisabetta; Barbani, Niccoletta; Frati, Caterina; Madeddu, Denise; Massai, Diana; Morbiducci, Umberto; Lazzeri, Luigi; Falco, Angela; Lagrasta, Costanza; Audenino, Alberto; Cascone, Maria Grazia; Quaini, Federico
Introduction: Injectable scaffolds are emerging as a promising strategy in the field of myocardial tissue engineering. Among injectable scaffolds, microparticles have been poorly investigated. The goal of this study was the development of novel gelatin/gellan microparticles that could be used as an injectable scaffold to repair the infarcted myocardium. In particular, the effect of particle size on cardiac progenitor cell response was investigated. Methods: Particles were produced by a water-in-oil emulsion method. Phosphatidylcholine was used as a surfactant. Particles with different diameter ranges (125–300 µm and 350–450 µm) were fabricated using two different surfactant concentrations. Morphological, physicochemical, and functional characterizations were carried out. Cardiac progenitor cell adhesion and growth on microparticles were tested both in static and dynamic suspension culture conditions. Results: Morphological analysis of the produced particles showed a spherical shape and porous surface. The hydrophilicity of particle matrix and the presence of intermolecular interactions between gellan and gelatin were pointed out by the physicochemical characterization. A weight loss of 75 ± 5 % after 90 days of hydrolytic degradation was observed. Injectability through a narrow needle (26 G) and persistence of the microparticles at the injection site were preliminarily verified by ex vivo test. In vitro cell culture tests showed a preservation of rat cardiac progenitor biologic properties and indicated a preferential cell adherence to microparticles with a smaller size. Conclusion: Overall, the obtained results indicate that the produced gelatin/gellan microparticles could be potentially employed as injectable scaffolds for myocardial regeneration.